Ecology and distribution of the grey notothen, Lepidonotothen squamifrons, around South Georgia and Shag Rocks, Southern Ocean. Issue 3 (26th November 2013) - Gregory, Susan; Brown, Judith; Belchier, Mark
Abstract New information on the biology and ecology of an abundant 'rockcod' species, Lepidonotothen squamifrons (family: Nototheniidae), found at South Georgia is presented. Data collected from twenty demersal trawl surveys carried out at South Georgia and Shag Rocks (sub-Antarctic) from 1986–2012 were analysed to investigate distribution, size, maturity and diet. Distribution was patchy with large aggregations in consistent high-density 'hotspots' to the east of Shag Rocks and to the west of South Georgia. Fish density was shown to vary between regions of the shelf and between years but there was little evidence of significant changes in catch per unit effort (CPUE) over the duration of the study. Length at first maturity for males and females (37–38 cm, total length) was very similar to that described for the Indian Ocean population. Detailed stomach contents analysis (2005–12) indicated a varied diet dominated by salps/tunicates, but with ontogenetic and depth variations in prey composition. Lepidonotothen squamifrons was shown to be an opportunistic bentho-pelagic forager. Enhanced knowledge of the ecology of L. squamifrons will be valuable in future research on food web modelling and marine spatial management in the Southern Ocean and to provide baseline data on the ecology of the species in a rapidly changing environment.